The Origin of Apollo - Again - Bachvarova, Mary R. (Res antiquae, 2022)
The deity Appaluwa, who appears in the Arzawan plague rituals CTH 424.4. and 5, is added to the discussion of the origin of the Greek god Apollo alongside the Wilusan city god Appaliuna. The etymology of the Greek name is discussed anew in light of this new datum. The two rituals are analyzed in the larger context of plague rituals, Arzawan rituals, and magic rituals involving a dKAL, to show that Appaluwa should be considered to share in the morphology of dKAL, an archer deity associated with augury who has obvious parallels with the Iliadic Apollo.